(untitled) (Journal of Geography and Environmental Management, 2021)
The article presents the results of the accuracy assessment of the method of generalized integrated assessment for solving the inverse problem of a comprehensive environmental assessment of territories. It is called the generalized assessment because the objective functions include the numerical expression of the sums of the areas of each level of anthropogenic disturbance, first throughout the region, and then for areas with an oil and gas producing complex, referred to the area of the whole region or the sum of the areas of zones with an oil and gas production complexes. For the completeness of the perception-of-the-method, the-article-also describes methods for obtaining particular and private target functions, on the basis of which a generalized estimate is constructed Loads of transformation levels in private objective functions take into account the level of complexity of environmental protection measures for each component-of-the natural environment. The substantiation of weight loads in the private target functions is based on a review-of-literary sources analyzing intrasystemic relationships in the natural environment. The impact of the possible subjectivity of expert assessments in determining the loads (role) of the components of the environment in integrated environmental assessments in the form of objective functions is assessed by comparing various options for their sets. The-calculation-of-results showed that the proposed method for the generalized solution of the inverse problem of a comprehensive environmental-assessment-of-the-territory practically does not respond to changes in the loads on the components of-the environment, since this influence is leveled out by the procedure of subtracting the integral target function throughout the territory from its analogue for zones with oil and gas production complex.